Latar Belakang Historis Metode,Pendekatan Dan Corak Tafsir - Muh.Haslam Hafid; Halimah Basri; Muhammad Irham (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The study of Qur’anic exegesis (tafsir) has developed dynamically in response to historical changes, the evolving needs of Muslim societies, and the increasing complexity of contemporary issues. This study aims to examine the historical background of the emergence of methods, approaches, and trends in Qur’anic exegesis and to trace their development from the classical to the contemporary period. This research employs a qualitative library research method using descriptive analysis of relevant literature on Qur’anic exegesis. The findings indicate that, during the early period of Islam, Qur’anic interpretation was predominantly based on transmitted reports (riwayah) derived from the Prophet Muhammad (peace be upon him), his Companions, and the Tabi’un. As Islamic civilization expanded and scholarly traditions developed, various interpretive methods emerged, including tahlili (analytical), ijmali (global), muqaran (comparative), and maudhu’i (thematic), along with diverse interpretive trends such as jurisprudential (fiqhi), theological (kalami), philosophical (falsafi), mystical (sufi), and socio-literary (adabi ijtima’i) exegesis. In the modern and contemporary periods, Qur’anic exegesis has further developed through interdisciplinary approaches that integrate Islamic studies, social sciences, humanities, and natural sciences. Therefore, the development of methods, approaches, and trends in Qur’anic exegesis reflects historical dynamics as well as the continuing efforts of Muslims to understand the Qur’an contextually. Keywords: Qur’anic exegesis, tafsir methods, tafsir approaches, tafsir trends, historical development. Abstrak Kajian tafsir Al-Qur’an mengalami perkembangan yang dinamis seiring dengan perubahan zaman, kebutuhan umat, serta kompleksitas persoalan yang dihadapi manusia. Penelitian ini bertujuan untuk mengkaji latar belakang historis munculnya metode, pendekatan, dan corak tafsir serta menelusuri perkembangannya dari masa klasik hingga kontemporer. Penelitian ini merupakan penelitian kepustakaan (library research) dengan pendekatan kualitatif yang dianalisis secara deskriptif melalui berbagai literatur yang berkaitan dengan kajian tafsir. Hasil penelitian menunjukkan bahwa pada masa awal Islam penafsiran Al-Qur’an didominasi oleh pendekatan riwayah yang bersumber dari Nabi Muhammad saw., para sahabat, dan tabi’in. Seiring meluasnya wilayah Islam serta berkembangnya tradisi keilmuan, lahir berbagai metode tafsir seperti tahlili, ijmali, muqaran, dan maudhu’i, disertai berkembangnya beragam corak tafsir, seperti fiqhi, kalami, falsafi, sufi, dan adabi ijtima’i. Pada era modern dan kontemporer, kajian tafsir semakin berkembang melalui pendekatan interdisipliner yang memadukan ilmu-ilmu keislaman, sosial, humaniora, dan sains. Dengan demikian, perkembangan metode, pendekatan, dan corak tafsir merupakan hasil dari dinamika sejarah serta respons terhadap kebutuhan umat dalam memahami Al-Qur’an secara kontekstual. Kata kunci: tafsir Al-Qur’an, metode tafsir, pendekatan tafsir, corak tafsir, perkembangan historis.